Paradiplomacy: Bangkitnya Aktor Lokal di Fora Internasional - Takdir Ali Mukti (The Politics : Jurnal Magister Ilmu Politik Universitas Hasanuddin, 2015)
Abstract : Paradiplomacy as a new phenomenon in international studies brings a large number of information, but it is very scarce in theoretical framework. Paradiplomacy as a part of transnational interactions grows rapidly around the world marking local awakening to face global affairs, and it offers opportunities and obstacles. Although this first symptom came from Europe, but nowadays, local governments in Indonesia also work in the same way. The problem is how Indonesian central government and local governments face that challenge.This article wants to explore paradiplomatic understanding, paradiplomacy’s experiences from several countries and paradiplomacy in Indonesia in the context of ASEAN Economic Community 2015.Keywords: Paradiplomacy, Local government, Sub-state, Transnational